Hybrid Manufacturing of Oral Solid Dosage Forms via Overprinting of Injection-Molded Tablet Substrates - Han Xu; Farnoosh Ebrahimi; Ke Gong; Zhi Cao; Evert Fuenmayor; Ian Major (MDPI AG, 2023)
Since 3D printing allows for patient-specific dosage forms, it has become a major focus in pharmaceutical research. However, it is difficult to scale up drug product manufacturing. Injection molding has been used in conjunction with hot-melt extrusion to mass produce drug products, but making tailored solid dosage forms with this technology is neither cost-effective nor simple. This study explored the use of a combination of fused filament fabrication and injection molding to create patient-specific solid dosage forms. A tablet fixation and location template was used to overprint directly on injection-molded tablet bases, and theophylline was combined with polycaprolactone and Kollidon® VA64 via hot-melt extrusion to produce the filament. Dynamic mechanical analysis was used to evaluate the brittleness of the filament, and differential scanning calorimetry was used to analyze the thermal results. The results showed that theophylline had a flow promoting effect on the polymer blend and that overprinted tablets were manufactured faster than 3D-printed tablets. Drug release studies also showed that overprinted tablets released faster than injection-molded tablets. This method demonstrates the potential of hybrid manufacturing for the pharmaceutical industry as a means of bridging the gap between personalized dosage forms and mass production.